Question
upstudy study bank question image url

5. Calculate the value of the expression \( 3 x^{2}+4 x-5 \) when \( \begin{array}{lll}\text { a) } x=-1 & \text { b) } x=-2 & \text { c) } x=0\end{array} \)

Ask by Ayala Moran. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

When \( x = -1 \), the expression \( 3x^{2} + 4x - 5 \) equals **-6**. When \( x = -2 \), the expression equals **-1**. When \( x = 0 \), the expression equals **-5**.

Solution

Sure, let's evaluate the expression \( 3x^{2} + 4x - 5 \) for each given value of \( x \). ## Expression: \[ 3x^{2} + 4x - 5 \] ## a) When \( x = -1 \): 1. **Substitute** \( x = -1 \) into the expression: \[ 3(-1)^{2} + 4(-1) - 5 \] 2. **Calculate the exponent**: \[ (-1)^{2} = 1 \] So, \[ 3(1) + 4(-1) - 5 \] 3. **Multiply**: \[ 3 \times 1 = 3 \] \[ 4 \times (-1) = -4 \] Now, \[ 3 - 4 - 5 \] 4. **Add/Subtract**: \[ 3 - 4 = -1 \] \[ -1 - 5 = -6 \] **Result**: \[ 3(-1)^{2} + 4(-1) - 5 = -6 \] --- ## b) When \( x = -2 \): 1. **Substitute** \( x = -2 \) into the expression: \[ 3(-2)^{2} + 4(-2) - 5 \] 2. **Calculate the exponent**: \[ (-2)^{2} = 4 \] So, \[ 3(4) + 4(-2) - 5 \] 3. **Multiply**: \[ 3 \times 4 = 12 \] \[ 4 \times (-2) = -8 \] Now, \[ 12 - 8 - 5 \] 4. **Add/Subtract**: \[ 12 - 8 = 4 \] \[ 4 - 5 = -1 \] **Result**: \[ 3(-2)^{2} + 4(-2) - 5 = -1 \] --- ## c) When \( x = 0 \): 1. **Substitute** \( x = 0 \) into the expression: \[ 3(0)^{2} + 4(0) - 5 \] 2. **Calculate the exponent**: \[ (0)^{2} = 0 \] So, \[ 3(0) + 4(0) - 5 \] 3. **Multiply**: \[ 3 \times 0 = 0 \] \[ 4 \times 0 = 0 \] Now, \[ 0 + 0 - 5 \] 4. **Add/Subtract**: \[ 0 + 0 = 0 \] \[ 0 - 5 = -5 \] **Result**: \[ 3(0)^{2} + 4(0) - 5 = -5 \] --- ## Summary of Results: - **a)** When \( x = -1 \), the expression evaluates to **-6**. - **b)** When \( x = -2 \), the expression evaluates to **-1**. - **c)** When \( x = 0 \), the expression evaluates to **-5**.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To calculate the value of the expression \( 3 x^{2}+4 x-5 \) for the given values of \( x \): a) When \( x = -1 \): \[ 3(-1)^{2}+4(-1)-5 = 3(1) - 4 - 5 = 3 - 4 - 5 = -6 \] b) When \( x = -2 \): \[ 3(-2)^{2}+4(-2)-5 = 3(4) - 8 - 5 = 12 - 8 - 5 = -1 \] c) When \( x = 0 \): \[ 3(0)^{2}+4(0)-5 = 0 + 0 - 5 = -5 \] So, the values are: a) -6, b) -1, c) -5.

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy